Avaliação de tecnologia assistiva para cegos : enfoque na prevenção ao uso de drogas psicoativas - Cezario, Kariane Gomes (2009)
Technologies for nursing care delivery to blind people include assistive technology (AT). The development and use of this type of technology can be a tool for health promotion and information provision with a view to improving the health communication process. An earlier study developed a health AT on the prevention of psychoactive drugs consumption among blind people, mediated by distance access. As the AT was accepted, the researchers decided to subject it to a deeper expert assessment study. Among different options, Pasquali’s (1999) model is a possible theoretical-methodological reference framework for technology assessment. In this study, the phases of the theoretical pole elaborated by this author will be followed. Thus, the goal was to assess some points of the AT, such as: aspects of content on psychoactive drugs; pedagogical aspects related to accessibility for blind people; and technical aspects related to distance access issues. A descriptive technology assessment research was carried out between March and September 2009, using the infrastructure of the Health Communication Laboratory at Ceará Federal University (LabcomSaúde-UFC). Nine expert judges participated, totalling three for each respective area of content about drugs, special education with emphasis on education for the blind and distance access. Each group of judges worked on one phase, with one phase following the other, as these professionals elaborated their assessments, the researcher made adjustments, which were then resubmitted to the professionals’ assessment. Three assessment instruments were constructed, whose items addressed specificities of each area and its items, with scores ranging from one to four, defined as follows: adequate, partially adequate, inadequate and does not apply. All judges signed the Free and Informed Consent Term. The content experts’ assessments pointed towards the quality of the AT’s content and requested orthographic corrections, improvements in some concepts and clarifications of technical terms. The pedagogical aspect judges considered all aspects as adequate. Nevertheless, they suggested improvements in voice synthesizers, tools needed for the blind to have computer access, as well as the inclusion of audio material, inviting participants to access the technology. Finally, the technical aspect judges indicated the need to include graphic and multimedia tools. These suggestions were not readily accepted because, in a sense, they go against literature on aspects of distance access by blind people. In view of all of these considerations, the AT was properly assessed as a viable and afe means for health information provision about psychoactive drugs to blind people. Thus, as detailed, blind people can access the AT individually, whenever and as many times as they want. The technology was considered interesting, collaborating in the learning process and a useful tool for health promotion and communication mediated by distance access. The suggestions collaborated to strengthen access to this technology.